2020
DOI: 10.3390/vaccines8020175
|View full text |Cite
|
Sign up to set email alerts
|

Anal Human Papillomavirus Infection among MSM Attending University in China: Implications for Vaccination

Abstract: Men who have sex with men (MSM) attending university are a high-risk population for human papillomavirus (HPV) infection and are a neglected population of HPV vaccination programs in China. To provide evidence for HPV vaccination policies, we conducted this study to examine the prevalence and factors associated with anal HPV infection among MSM attending university in China. A self-administered online questionnaire was conducted to collect information on social demographics and sexual behaviors. A self-collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The prevalence of high-risk HPV single infection was 47.8%. Corresponding values for women and for HIV-infected men who have sex with men range from 37.5% (Fan et al, 2020). Among high-risk HPV types, we found HPV 58 to be the most common, followed by HPV 18, HPV 16 and HPV 33.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The prevalence of high-risk HPV single infection was 47.8%. Corresponding values for women and for HIV-infected men who have sex with men range from 37.5% (Fan et al, 2020). Among high-risk HPV types, we found HPV 58 to be the most common, followed by HPV 18, HPV 16 and HPV 33.…”
Section: Discussionmentioning
confidence: 78%
“…Among high-risk HPV types, we found HPV 58 to be the most common, followed by HPV 18, HPV 16 and HPV 33. The most common high-risk HPV types in HIV patients worldwide are HPV 16 followed by HPV 18 (Fan et al, 2020;Nasioutziki et al, 2020). Among Spanish MSM, the most prevalent high-risk HPV was HPV 31 and in China, HPV 58 were the most frequently detected (Torres et al, 2013;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As men appear not to develop immunity to HPV following natural infection, the reinfected HPV type will likely depend on the prevalence of the individual HPV types circulating in the community. Studies have reported that the most common high-risk HPV type among HIV-negative MSM were HPV52, 58, 16, and 18 ( 5 , 6 , 21 24 ). Therefore, it is understandable that HPV types 58, 52, and 16 had the highest rates of reinfection in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their frequent high-risk sexual behaviors, men who have sex with men (MSM) are at increased risk for anal HPV infection and HPV-related diseases (1-3), while persistent infection might induce precancerous lesions and cancers (4). The estimated prevalence of anal HPV among human immunodeficiency virus (HIV) negative MSM in China was 53.6%, and the most frequently detected HPV genotypes were HPV6, HPV16, HPV11, HPV52, and HPV58 (5)(6)(7). Several prophylactic HPV vaccines have been available since 2006, such as HPV-16/18 bivalent vaccine (Cervarix R , GSK, and Cecolin R , Xiamen Innovax), HPV-6/11/16/18 quadrivalent vaccine (Gardasil R , Merck), and HPV-6/11/16/18/31/33/45/52/58 nine-valent vaccine (Gardasil R 9, Merck).…”
Section: Introductionmentioning
confidence: 99%
“…Human immunodeficiency virus (HIV)-infected MSM are at exceptionally high risk of anal HPV infection and infection with multiple genotypes. [1][2][3][4][5][6] Other risk factors associated with HPV infection are smoking and sexual practices. 7 Until now there is no data available on the prevalence and distribution of HPV genotype in the MSM in Bali province and Indonesia.…”
Section: Introductionmentioning
confidence: 99%